KAJIAN PEMBERDAYAAN KAKAO RAKYAT MENJADI MASYARAKAT MANDIRI MELALUI AGROINDUSTRI - Lucyana Trimo; Syarif Hidayat; Lies Sulistyowati (Universitas Galuh Ciamis, 2020)
Government efforts to improve the competitiveness of Indonesian cocoa in the international world have been done by launching the National Cocoa Production Improvement and Quality Movement (GERNAS). In order for the GERNAS movement to take place, the development of the region needs to be done comprehensively, especially in the leading commodity centers, such as cocoa commodity in Luwu Raya in South Sulawesi Province, which still tends to produce cocoa beans (not in processed form) The people are more independent then empowerment should be directed to the agroindustry, and it becomes an urgent thing. To empower people's cocoa into an independent community based on cocoa agro-industry, it must be supported by its own cocoa commodities ranging from on-farm to off-farm that are interconnected with each other, and are integrative and sustainable. The research technique is descriptive survey approach. The selected research site is Luwu Raya in South Sulawesi Province. Data collection techniques were conducted by: library study and interview with related parties, ie officials at government institutions, cooperatives, manufacturers, associations of cocoa farmers, and farmers groups selected purposively. Secondary data mining is done by collecting: documents or transcripts in related institutions, and journals. Data and information obtained then analyzed by descriptive correlative. Based on the results of the research, empowering people's cocoa into an independent community through agro-industry becomes a necessity. In order to become an independent community, what should be done is: (a) transferring technology based on local potential, (b) facilitation of the government in the provision of bailouts and processing machines, and (c) support in the regulations in favor of the farmers.